Investigating the Role of Holistic Education in Global Learning: A Bibliometric Approach - Judijanto, Loso; Subroto, Desty Endrawati; Dumiyati, Dumiyati; Haryanti, Yuyun Dwi; Thalib, Najdah (The Eastasouth Journal of Learning and Educations, 2024)
This study investigates the role of holistic education in global learning using a bibliometric analysis approach. Drawing data from 1,000 articles published between 1970 and 2024, this analysis identifies key themes, influential authors, and collaboration patterns in the field of holistic education. The findings reveal that holistic education research is centered on themes like higher education, sustainability, and transformative learning, reflecting the field's response to global challenges. Collaboration networks show strong international partnerships, with notable contributions from the United States, United Kingdom, and emerging interest in Asian countries. The analysis also highlights the application of holistic education in specialized areas such as medical and nursing education, emphasizing its relevance to fostering well-rounded professionals. However, challenges persist in assessment methods, cultural adaptability, and technological integration, indicating areas for future research. This study provides a comprehensive overview of holistic education, underscoring its potential to address the educational needs of a globalized world while identifying critical directions for further development.